Evaluation of different methods to detect methicillin resistance in Staphylococcus aureus (MRSA) - Farzad Alipour; Malahat Ahmadi; Shahram Javadi (Elsevier, 2014)
Summary: The studies suggest that dogs living with human are potential risk of becoming MRSA carrier and increased risk of infections caused by MRSA. Phenotypic methods to detect methicillin resistance in Staphylococcus aureus (MRSA) are inadequate. The objective of the present study was to determine methicillin resistance in S. aureus by phenotypic susceptibility test (oxacillin disk diffusion, cefoxitin disk diffusion, oxacillin screen agar) and molecular methods (PCR as a gold standard) and the latex agglutination test for the detection of PBP2a and to evaluate the results of these tests for its sensitivity and specificity. A total of 100 swab samples were taken from muzzle site, in more contact with human, of dogs and MRSA were isolated. Oxacillin (1 μg), cefoxitin (30 μg) disk diffusion and oxacillin screen agar method were used. The isolates were also subjected to latex agglutination test for detection of PBP2a and PCR to detect mecA gene.By PCR 37% of isolates show the presence of mecA. Latex agglutination was found to be the most sensitive (97.29%) and cefoxitin disk diffusion to be the most specific (96.82%) tests for detection of MRSA. Our finding showed that combining oxacillin screen agar or cefoxitin disk diffusion with latex agglutination improves sensitivity and specificity to detect methicillin resistance S. aureus (MRSA) isolates. Keywords: MRSA, mecA, Dogs, Phenotypic methods